2022
DOI: 10.1177/23259671221134091
|View full text |Cite
|
Sign up to set email alerts
|

Current Gender Diversity and Geographic Trends Among Orthopaedic Sports Medicine Surgeons in the United States

Abstract: Background: Female representation varies geographically among orthopaedic residency programs, with the southern region of the United States reported as having relatively lower rates of female orthopaedic surgeons. Purpose: To determine the gender and geographic distributions of US-based orthopaedic sports medicine surgeons and analyze geographic patterns between their training locations and present-day practices. Study Design: Cross-sectional study. Methods: American Orthopedic Society of Sports Medicine (AOSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Overall, orthopedic sports medicine had the most female applicants; however, the proportion of females in the applicant pool was third highest at 9.1% (n = 94), with pediatrics being the highest at 24.8% (n = 79). One additional study by Kocjan et al 27 used American Orthopaedic Society of Sports Medicine (AOSSM) completion data to extract the demographics of orthopedic sports medicine fellowship graduates from 2016 to 2021 and found that females comprised 11% (n = 141) of the graduates. Most recent data collected by Lavorgna et al 28 from the Arthroscopy Association of North America (AANA) fellowship directory states gender of orthopedic sports medicine fellows in the 2021-2022 academic year included 14.4% (n = 19) females.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, orthopedic sports medicine had the most female applicants; however, the proportion of females in the applicant pool was third highest at 9.1% (n = 94), with pediatrics being the highest at 24.8% (n = 79). One additional study by Kocjan et al 27 used American Orthopaedic Society of Sports Medicine (AOSSM) completion data to extract the demographics of orthopedic sports medicine fellowship graduates from 2016 to 2021 and found that females comprised 11% (n = 141) of the graduates. Most recent data collected by Lavorgna et al 28 from the Arthroscopy Association of North America (AANA) fellowship directory states gender of orthopedic sports medicine fellows in the 2021-2022 academic year included 14.4% (n = 19) females.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the 3 greatest influencers of subspecialty choice are enjoyment of procedures, proficiency in related surgical skills, and overall experiences with that field during residency program training. 35 , 36 , 37 Comparatively, mentorship plays less of a role in specialty selection, with only 21% of respondents to a survey of female fellowship-trained orthopaedic surgeons citing this as a significant impactor. However, it is true that mentorship is the primary modifiable factor in the decision-making process.…”
Section: Fellowship Programsmentioning
confidence: 99%